How to Construct Three-Dimensional Transport Theory Using Rotated Reference Frames. Issue 7 (9th November 2016) - Machida, Manabu
ABSTRACT: In linear transport theory, 3D equations reduce to 1D equations by means of rotated reference frames. In this paper, we illustrate how the technique works and 3D transport theories are obtained.